Zooming into cosmetic procedures during the COVID-19 pandemic: The provider’s perspective - Shauna M. Rice, BS; Julia A. Siegel, MD; Tiffany Libby, MD; Emmy Graber, MD, MBA; Arianne Shadi Kourosh, MD, MPH (International Journal of Women's Dermatology, 2021)
The COVID-19 pandemic has seen a massive shift toward virtual living, with video-conferencing now a primary means of communication for both work and social events. Individuals are finding themselves staring at their own video reflection, often for hours a day, scrutinizing a distorted image on screen and developing a negative self-perception. This survey study of over 100 board-certified dermatologists across the country elucidates a new problem of Zoom dysmorphia, where patients seek cosmetic procedures to improve their distorted appearance on video-conferencing calls.